The resource curse and duties to immigrants - Tamara Crnko (Taylor & Francis Group, 2021)
This paper brings together the discussions on international resource trade and immigration. Following Wenar’s analysis of the resource curse, the aim is to challenge the conventional view on immigration that asserts the right of states to have discretionary control over these policies. The paper shows that more liberal immigration is required as an additional remedial policy to persons harmed in unjust trade. The right to self-determination and territorial rights, which are used as the basis for the exclusion of immigrants, are in the context of this analysis constrained by both attentiveness to harm and the charge of inconsistency. Both rights, which are protected domestically, are violated by the unjust ‘might makes right’ trade rule in the international context, causing harm to people in resource exporting countries. This inconsistency presents a challenge to the moral plausibility of the conventional view in the context of the resource trade.